DAYA TARIK WISATA CANDI MUARA TAKUS KABUPATEN KAMPAR RIAU - Anggara, Putra Yuda; Sulistyani, Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Attraction is an important factor of a tourism area. There are 2 factors of tourist attraction, namely tangible and intangible. This study aims: (1) to know the tourist attraction of Muara Takus Temple, Kampar Regency, Riau; (2) to know the management efforts to maintain the Cultural Heritage of the Muara Takus Temple in Kampar Regency, Riau. This study uses a qualitative method with a descriptive approach which the research’s subjects are community leaders or traditional leaders, Village Heads, POKDARWIS, and Cultural Heritage Conservation Centers. Data collection was done by doing document study, observation, and interview while the data analysis used data reduction, data presentation, and conclusion drawing. The result showed that the Muara Takus Temple has tangible and intangible tourist attraction. The tangible attraction consisted of the physical form of buildings including monuments, building groups and sites, while the itangible tourist attraction built by cultural values from the past including traditions, folklore and legends, mother tongue, and oral history of creativity (dance, songs, and performances). It can be concluded that the Muara Takus Temple has the potential to be developed as a tourist attraction by utilizing the existing tangible object and maintain the preservation of cultural heritage.Keyword: Tourism attraction, Muara Takus temple